Prioritising non-native pest species to inform plant health biosecurity policy decisions and to safeguard agriculture, forestry, biodiversity, and livelihoods in Uganda - Mulema, Joseph; Nankinga, Caroline; Kagorora, John Patrick Kanahe; Tusiime, Geoffrey; Amayo, Robert; Chemonges, Martin; Gumisiriya, Costa; Kato, Fred; Kigongo, Boniface Mulindwa; Kutunga, David; Mudde, Barnabas; Muhumuza, John Bosco; et al. (Frontiers in Agronomy, 2025)
In recent years, various invasive species have been introduced to sub-Saharan Africa, partly due to insufficient information about potential invasions, which has led countries to respond reactively rather than proactively. This information can be gathered through horizon scanning. Using the CABI Horizon Scanning Tool, 9,071 pest species have been identified as unreported in Uganda. A subset of 1,517 was prioritised for rapid risk assessment based on guidelines that evaluated the likelihood of entry and establishment, the magnitude of socio-economic and environmental impact, as well as potential pathways of introduction. These pest species included 357 arthropods, 130 bacteria, 74 chromista, 417 fungi, 19 molluscs, 124 nematodes, nine protists, and 387 viruses and viroids, of which 360 of the 1,517 were reported as invasive. Vectors and vectored organisms were also assessed to determine their associated risk. Management actions were recommended for 618 species, which included 160 arthropods, 70 bacteria, 30 chromista, 174 fungi, six molluscs, 41 nematodes, three protists, eight viroids, and 126 viruses. These pest species either attained an overall risk score of 54 and above or a lower score for specific pest species. The actions included targeted surveillance, regulation supported by pest risk analysis, contingency planning, publicity, management by the industry, and research. This information is vital for risk monitoring and management and can be utilised by countries in the East African Region.